THE EFFECT OF COCOA LEAVES FEEDING ONT HE WEIGHT GAIN OF GOATS (STUDY ON FARMERS IN THE BANJARHARJO VILLAGE, KULON PROGO) - Gunawan Gunawan; Wiendarti Indri Werdhany1; I Gede Suparta Budisatria (Buletin Peternakan, 2017)
Cocoa leave is potential as goat’s feed, but has not been widely used by farmers. The aim of this study was to observe the use of cocoa leaves as goat feed and their effect on the daily gain of goats. This study was conducted on 2 phases. Phase 1, study of the use of cocoa leaves as feed goat has been done on 10 farmers with innovation and 10 farmers without innovation. The observations were done by weighing of fresh cocoa leaves as goat feed for eight months (March to October, 2013). Independent t-test was done to analyze the cocoa leaves treatments on farmers with and without innovation . Phase 2, feeding trial has been done for 8 weeks to compare 3 level of feed treatments namely A (grass ad lib, cocoa leaves 2 kg/head/day, rice bran 0.6 kg/head/day), B (grass ad lib, cocoa leaves 2 kg/head/day) and C (grass ad lib). Each level of feed treatment consisted of 7 male Bligon goats, aged 11-12 months. Data was analyzed using analysis of covariance with initial body weight as covariate. The results showed that the use of cocoa leaves as goat feed on farmers  with innovations was 130 ± 18 g/head/day higher than on farmers without innovation namely 33 ± 19 g/head/day. Body weight gain of goat increased from 30,6 ± 13,5 g/head/day (feeding grass) to 61,2 ± 9,5  g/head/day if added cocoa leaves 2 kg/head/day and to 68,9 ± 24,0g/head/day if added cocoa leaves 2 kg/head/day and rice bran 0.6 kg/head/day. The study implied that cocoa-goats integration system should be developed to optimize the utilization of cocoa leaves as goat’s feed.